EFFECT OF 12 WEEKS OF HOME BASED EXERCISES ON BODY COMPOSITIONS IN OVERWEIGHT AND OBESE WOMEN - MANISHA A. RATHI,; Dr. ALI IRANI,; Dr. V. A. KAKRANI, (International Journal of Pharma and Bio Sciences, 2016)
Background of the study:- Women were more vulnerable to obesity epidemic than men. Time and cost can be the barriers in reducing obesity. Exercises in home environment can help in reducing weight and body fat. Hence objective of this study was to find out the efficacy of home based exercises in women. Methodology:- In this experimental study design, 110 overweight and obese women were selected. Home based exercises including 30 min. walking plus 15 min. mat exercises were explained and 2 sessions were practiced and they were instructed to do the exercises for 5 days/week for 12 weeks at home. Body compositions like Weight, Body Mass Index (BMI) and Percentage of body fat were measured before and after the exercises. Statistical significance was considered at 95 % Confidence Interval. Result:- Mean weight was reduced significantly in women (2.20 + 1.38 Kg). Pre weight was 65.11 + 8.5 Kg. whereas post weight was 62.61 + 8.2 Kg. Mean BMI was also reduced significantly as p<0.01. Pre and post BMI in women was 26.54 and 25.65 kg/m2. Percentage of body fat also show significant reduction in 12 weeks. Conclusions: Women showed positive response to home based exercises on body composition. As it is cost effective and flexible in timings and venue, it can be easily practiced in community.